Determinant of Students’ Academic Satisfaction - Khoirina, Amanatun; Rusdarti, Rusdarti; Rozi, Fahrur (Universitas Negeri Semarang, 2020)
This study aims to analyze the effect of the quality of service, educational fees, facilities and infrastructures towards the students’ academic satisfaction and to analyze its influence which can be moderated by the image towards the students’ academic satisfaction at the Economics and Business Faculty of STIKUBANK university. The method of the research is a quantitative approach. The population of the study are 2467 students of the Faculty of Economics and Business, University of STIKUBANK Semarang, with a total sample are 96 respondents. The data collection used is a questionnaire. The methods of data analysis are descriptive analysis and hypothesis testing with moderation regression analysis (absolute value test). The results shows that there is influence on the quality of service, educational fees, facilities and infrastructures towards the students’ academic satisfaction, while the effect is positive and significant. Image variable does not moderate the effect of quality of service on the students’ academic satisfaction.